Identification of hypoxia-induced genes in human SGBS adipocytes by microarray analysis. - Kathrin Geiger (Public Library of Science (PLoS), 2011)
Hypoxia in adipose tissue is suggested to be involved in the development of a chronic mild inflammation, which in obesity can further lead to insulin resistance. The effect of hypoxia on gene expression in adipocytes appears to play a central role in this inflammatory response observed in obesity. However, the global impact of hypoxia on transcriptional changes in human adipocytes is unclear. Therefore, we compared gene expression profiles of human Simpson-Golabi-Behmel syndrome (SGBS) adipocytes under normoxic or hypoxic conditions to detect hypoxia-responsive genes in adipocytes by using whole human genome microarrays. Microarray analysis showed more than 500 significantly differentially regulated mRNAs after incubation of the cells under low oxygen levels. To gain further insight into the biological processes, hypoxia-regulated genes after 16 hours of hypoxia were classified according to their function. We identified an enrichment of genes involved in important biological processes such as glycolysis, response to hypoxia, regulation of cellular component movement, response to nutrient levels, regulation of cell migration, and transcription regulator activity. Real-time PCR confirmed eight genes to be consistently upregulated in response to 3, 6 and 16 hours of hypoxia. For adipocytes the hypoxia-induced regulation of these genes is shown here for the first time. Moreover in six of these eight genes we identified HIF response elements in the proximal promoters, specific for the HIF transcription factor family members HIF1A and HIF2A. In the present study, we demonstrated that hypoxia has an extensive effect on gene expression of SGBS adipocytes. In addition, the identified hypoxia-regulated genes are likely involved in the regulation of obesity, the incidence of type 2 diabetes, and the metabolic syndrome.